Pengaruh Bauaran Pemasaran Terhadap Keputusan Pembelian Serta Implikasinya pada Kepuasan Konsumen - Sarah Sinta; Ferryal Abadi (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of product, price, distribution, and promotion on purchase intention Hydro Coco isotonic drinks. And also want to know the influence of purchase interntion on customer satisfaction. This study used a quantitative approach through survey of 85 respondents. The sample population was the 2015 class of Management Faculty Kalbis Institute students who were active in the even semester semester 2019. Using the Slovin formula with margin error of 5%. Hypothesis test results (t test) which show that the product, price, distribution, and promotion partially have a positive and significant influence on purchasing intention. And there is a positive and significant influence between purchase intention on customer satisfaction. The conclusion of this study is that price is the most dominant variable for purchase intention. This can be interpreted that the price is the only element of the marketing mix that is often used as consideration in making a purchase.